SMILE: Sherlock Holmes in Switzerland - Patrick Buechel; Laura Loder Buechel (Babylonia, 2024)
With the death of Sherlock Holmes at the Reichenbach Falls in Meiringen, Switzerland, Arthur Conan Doyle forged the enduring love of Sherlock Holmes in Swiss schools. And why not make this connection even stronger by visiting one of the two Sherlock Holmes museums during a class camp or otherwise? With plenty to do in the Meiringen and Lucens areas, a short museum visit can help learners make connections to the stories and movies they have worked with in English lessons in the classroom and provide a short break from all the hiking and outdoor activities or provide a rainy-day activity!